Preparation and Structural Properties of Free Films from Rapeseed Oil-Based Rigid Polyurethane-Montmorillonite Nanocomposites - Sergey Gaidukov; Ugis Cabulis; Karina Gromilova; Velta Tupureina; Agnese Grigalovica (International Journal of Polymer Science)
The preparation of free standing films of biobased rigid polyurethanes (PU) from rapeseed oil (RO) and diethanolamine (DEA) polyol and its modification with organomontmorillonite (OMMT) nanoparticles are described. Heat enthalpy of the interaction during in situ mixing of RO/DEA polyol and OMMT is measured in isothermal profile. The Fourier transform infrared spectral analysis (FTIR-ATR) is used to determine the urethane group concentration and hydrogen bonds formation in PU and PU/OMMT nanocomposites. X-ray diffraction shows the formation of intercalated and exfoliated structures of OMMT. The glass-transition temperature is used to demonstrate the formation for the intercalated and exfoliated nanocomposites of an interphase with a possible compact structure and the altered polymer chain mobility. The prepared PU/OMMT nanocomposites are also characterized by the enhanced thermal degradation characteristics upon heating in air atmosphere.